Knowledge and Attitude of Short Stature and Its Treatment in Saudi Arabia - Hashem, Majdi; AlMohaini, Reem Abdulrahman (Faculty of Medicine, Universitas Padjadjaran, 2023)
Both tall and short parents are concerned about their children's short stature. This study aimed to explore the knowledge about short stature (SS) and attitude towards its treatment among the general public of Saudi Arabia. This was a cross-sectional study that utilized an online-administered questionnaire distributed between August 2021 and March 2022. Binary logistic regression was conducted to identify factors that affect participants’ knowledge. This study included a total of 6,852 individuals. The vast majority of the participants (77.5%) expressed satisfaction with their height. A total of 40.4% of participants stated that they were aware of a treatment option for their low height. With a mean score of 13.0 (SD:5.8) out of 25, the participants demonstrated a moderate level of knowledge of short stature (52.0%). The majority of participants (78.0%) stated that if they have a problem with short stature or want to enhance their own or their children's height, they are willing to consult a doctor about it. Participants living in the northern and eastern areas, those with bachelor degree, and those working in the healthcare field were more likely to be knowledgeable about short stature compared to others (p≤0.01). Saudi Arabians have a moderate understanding of SS, which needs to be improved. Campaigns to increase the general public's and parents' knowledge about SS, which is ultimately connected to earlier diagnosis and better management outcomes, are needed. Additional research is required to examine the most effective strategies for raising public knowledge of SS.